Suppressing Halide Segregation Via Dual-Anchoring Strategy for 31.20% Perovskite/Silicon Tandem Solar Cells - Du, Hao; Li, Jiawen; Ma, Zhu; Zhang, Qian; Gou, Fuchun; Li, Yixian; Chen, Bo; Lv, Zhuo; Xiang, Dengqian; Hou, Shanyue; Chen, Yi; Du, Zhuowei; et al. (Advanced Energy Materials, 2025)
The efficiency and stability of wide bandgap (WBG) perovskite solar cells (PSCs) are constrained by photo-induced halide segregation and severe non-radiative recombination, which significantly impedes the advancement of high-efficiency and stable perovskite/silicon tandem solar cells (PSTSCs). In this work, a potassium 4-sulfonic-1,8-naphthalic anhydride salt (4S-NAPS), featuring dual-anchoring sites, is incorporated into the perovskite precursor. The sulfonic group (─SO3−) and carbonyl group (C═O) interact with uncoordinated Pb2+ ions on the perovskite surface. In addition, K⁺ ions occupy interstitial sites within the crystal lattice, thereby effectively enhancing the ion migration barrier and suppressing halide phase separation. Owing to the dual-anchoring effect of 4S-NAPS, a single-junction WBG PSC (1.68 eV) delivers a power conversion efficiency (PCE) of 22.95% and an open-circuit voltage (VOC) of 1.26 V, representing one of the highest efficiencies reported for WBG PSCs. Moreover, the unencapsulated modified devices retain 90% of initial efficiency after 3000 h in a nitrogen atmosphere, demonstrating remarkable operational stability. Notably, the fabricated monolithic PSTSC achieves a PCE of 31.20%, a VOC of 1.950 V, and exhibits negligible hysteresis. This dual-anchoring strategy provides a promising avenue for fabricating highly efficient and stable WBG PSCs and offers new insights into achieving superior performance in PSTSCs.
Keywords: dual-anchoring strategy; halide segregation; high efficiency; perovskite/silicon tandem solar cells; wide-bandgap perovskite